Wolbachia and host intrinsic reproductive barriers contribute additively to postmating isolation in spider mites. (1st August 2021) - Cruz, Miguel A.; Magalhães, Sara; Sucena, Élio; Zélé, Flore
Abstract: Wolbachia are maternally‐inherited bacteria that induce cytoplasmic incompatibility in many arthropod species. However, the ubiquity of this isolation mechanism for host speciation processes remains elusive, as only few studies have examined Wolbachia ‐induced incompatibilities when host populations are not genetically compatible. Here, we used three populations of two genetically differentiated colour forms of the haplodiploid spider mite Tetranychus urticae to dissect the interaction between Wolbachia ‐induced and host‐associated incompatibilities, and their relative contribution to postmating isolation. We found that these two sources of incompatibility act through different mechanisms in an additive fashion. Host‐associated incompatibility contributes 1.5 times more than Wolbachia ‐induced incompatibility in reducing hybrid production, the former through an overproduction of haploid sons at the expense of diploid daughters (ca. 75% decrease) and the latter by increasing the embryonic mortality of daughters (by ca. 49%). Furthermore, regardless of cross direction, we observed near‐complete F1 hybrid sterility and complete F2 hybrid breakdown between populations of the two forms, but Wolbachia did not contribute to this outcome. We thus show mechanistic independence and an additive nature of host‐intrinsic and Wolbachia ‐induced sources of isolation. Wolbachia may contribute to reproductive isolation in this system, thereby potentially affecting host differentiation and distribution in the field.